The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1978
DOI: 10.1111/j.1600-0447.1978.tb02392.x
|View full text |Cite
|
Sign up to set email alerts
|

The episodic nature of anxiety and its treatment with oxazepam

Abstract: The presentation of anxiety in clinical practice is examined, and it is concluded that many patients, perhaps a majority, experience fluctuating levels of anxiety. It is therefore suggested that therapy should be intermittent, according to this waxing and waning of symptoms. Most benzodiazepines are long‐acting, and are therefore unsuitable for this type of therapy, but oxazepam, which is short‐acting and has no active metabolites, is ideal for this purpose. It is proposed that such a regimen would minimize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Anxiety disorders other than panic as well as anxieties associated with somatic diseases often show a fluctuating course (Imlah, ; McCurdy, ; Rickels and Schweizer, ; Brenes et al ., ; Cukor et al ., ), and it was suggested that patients showing fluctuating levels of anxiety may benefit from intermittent treatment especially with benzodiazepines that have a rapid onset of action (Imlah, ; McCurdy, ; Rickels and Schweizer, , ; Rouillon, ). On the other hand, nearly half of patients with psychiatric disorders (especially those suffering from depression and anxiety) prefer alternative therapies over conventional ones (Astin, ; Ben‐Arye et al ., ; Giordano et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety disorders other than panic as well as anxieties associated with somatic diseases often show a fluctuating course (Imlah, ; McCurdy, ; Rickels and Schweizer, ; Brenes et al ., ; Cukor et al ., ), and it was suggested that patients showing fluctuating levels of anxiety may benefit from intermittent treatment especially with benzodiazepines that have a rapid onset of action (Imlah, ; McCurdy, ; Rickels and Schweizer, , ; Rouillon, ). On the other hand, nearly half of patients with psychiatric disorders (especially those suffering from depression and anxiety) prefer alternative therapies over conventional ones (Astin, ; Ben‐Arye et al ., ; Giordano et al ., ).…”
Section: Discussionmentioning
confidence: 99%